Gene Pyramiding for Achieving Enhanced Resistance to Bacterial Blight, Blast, and Sheath Blight Diseases in Rice - Ramalingam, Jegadeesan; Raveendra, Chandavarapu; Savitha, Palanisamy; Vidya, Venugopal; Chaithra, Thammannagowda Lingapatna; Velprabakaran, Senthilvel; Saraswathi, Ramasamy; Ramanathan, Ayyasamy; Arumugam Pillai, Madhavan Pillai; Arumugachamy, Samudrakani; Vanniarajan, Chockalingam (Frontiers in Plant Science, 2020)
Bacterial blight, blast, and sheath blight are the commonest diseases causing substantial yield loss in rice around the world. Stacking of broad-spectrum resistance genes/QTLs in to popular cultivars is becoming a major objective of any disease resistance breeding programme. The varieties ASD 16, and ADT 43 are the two popular, high yielding, and widely grown rice cultivars of South India, which are susceptible to bacterial blight (BB), blast, and sheath blight diseases. The present study was carried out to improve the cultivars (ASD 16, and ADT 43) through introgression of bacterial blight (xa5, xa13, and Xa21), blast (Pi54), and sheath blight (qSBR7-1, qSBR11-1, and qSBR11-2) resistance genes/QTLs by MABB (Marker-assisted backcross breeding). IRBB60 (xa5, xa13, and Xa21) and Tetep (Pi54; qSBR7-1, qSBR11-1, and qSBR11-2) were used as donors to introgress BB, blast, and sheath blight resistance in to the recurrent parents (ASD 16, and ADT 43). Homozygous (BC3F3 generation), three-gene bacterial blight pyramided (xa5 + xa13 + Xa21) lines were developed and these lines were crossed with Tetep to combine blast (Pi54) and sheath blight (qSBR7-1, qSBR11-1, and qSBR11-2) resistance. In BC3F3 generation the lines (Improved pyramided lines), with a combination of xa5 + xa13 + Xa21+ Pi54 + qSBR7-1 + qSBR11-1 + qSBR11-2 were selected through molecular and phenotypic assay and these were evaluated for physical resistance against bacterial blight, blast, and sheath blight pathogens under greenhouse conditions. We have selected 9 lines in ASD 16 background and 15 lines in ADT 43 background, exhibiting high degree of resistance to BB, blast, and sheath blight diseases and also possessing phenotypes of recurrent parents. The improved pyramided lines are expected to be used as improved varieties or used as a potential donor in breeding programs.